Media flash flipbook for an interactive and immersive learning experience - Hamidah, Hamidah; Asrohah, Hanun Asrohah (Early Publishing, 2025)
Traditional learning, which focuses solely on lecture methods and texts, is now being replaced by more interactive and technology-based approaches. One increasingly popular approach is digital media-based learning, which emphasizes interactive and immersive learning experiences. Learning media must be packaged attractively so that students do not easily become bored with the material, one example being the Flash flipbook. The research method used in the preparation of this article is literature study (Library Research), which involves collecting data obtained through studies of existing literature relevant to the topic being examined by the researcher, falling under the category of qualitative research. Technological advancements have transformed the simplicity of flipbooks into something more engaging. The advantages of Flash flipbooks include the ability to incorporate files such as videos, moving images, or animations, which greatly assist in the learning process and help keep students engaged. Immersive learning can be found in Flash flipbook learning media, such as VR and AR. Flash flipbooks have been shown to enhance students' understanding, engagement, and motivation. The strengths of Flash flipbooks include the ease of presenting material in a concise and flexible manner.